2013
DOI: 10.1093/gbe/evt169
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Evolution of the Pathogenic Wolbachia Strain, wMelPop

Abstract: Most strains of the widespread endosymbiotic bacterium Wolbachia pipientis are benign or behave as reproductive parasites. The pathogenic strain wMelPop is a striking exception, however: it overreplicates in its insect hosts and causes severe life shortening. The mechanism of this pathogenesis is currently unknown. We have sequenced the genomes of three variants of wMelPop and of the closely related nonpathogenic strain wMelCS. We show that the genomes of wMelCS and wMelPop appear to be identical in the nonrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
126
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 64 publications
(116 reference statements)
10
126
1
Order By: Relevance
“…A further group of contigs included Wolbachia membrane proteins, and ankyrin genes, which are used to attach the bacterial membrane to the host cytoskeleton. These genes likely represent part of the machinery used to mediate Wolbachia -host interactions [39], are typically present in large numbers in Wolbachia genomes [35, 38, 4042], and may also be involved in CI [43]. …”
Section: Resultsmentioning
confidence: 99%
“…A further group of contigs included Wolbachia membrane proteins, and ankyrin genes, which are used to attach the bacterial membrane to the host cytoskeleton. These genes likely represent part of the machinery used to mediate Wolbachia -host interactions [39], are typically present in large numbers in Wolbachia genomes [35, 38, 4042], and may also be involved in CI [43]. …”
Section: Resultsmentioning
confidence: 99%
“…However there has been little change in cytoplasmic incompatibility caused by the infection or infection frequency in natural infected populations where a combination of maternal transmission leakage and cytoplasmic incompatibility dictates the expected frequency of the infection [7]. Moreover, genomic data point to little change in the w MelPop infection across 4 years after transfer into A. aegypti mosquitoes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Opposite to mentioned benefit, Wolbachia laboratory strain wMelPop, accidently obtained by irradiation of males during the early study of Hannah (1949), has an exceptional ability to shorten the lifespan of a host, causing severe nerve and muscle tissue degeneration (Min & Benzer, 1997). Recently it was shown that the amplification of a specific region in wMelPop genome might be the reason of its strong pathogenic phenotype (Chrostek et al, 2013;Woolfit et al, 2013). Its rapid over-replication within the host tissues, especially in the brain, makes this strain unique, attractable to scientists and very promising candidate for biological control.…”
Section: Introductionmentioning
confidence: 99%